THE DISTRIBUTION OF BENTHIC FORAMINIFERA IN CORAL REEFS COMMUNITY AND SEAGRASS BAD OF BELITUNG ISLANDS BASED ON FORAM INDEX - Suhartati M. Natsir; Mukhammad Subkhan (JOURNAL OF COASTAL DEVELOPMENT, 2011)
To check the feasibility of the environmental for coral reefs, several monitoring strategies exist, one of which making use of the foraminiferal community structure: FORAM Index, i.e. Foraminifera in Reef Assessment and Monitoring Index. The abundance of symbiont-bearing foraminifera should parallel coral abundance, if water quality is the major environmental control. This allows for the use of these foraminifera to quantify environmental quality with respect to coral health. The aim of this study is to study the benthic foraminiferal assemblages in coral reefs community and sea grass bad of Belitung Islands and to use that information to determine the environmental quality of their coral reefs based on FORAM Index. Sediments of Belitung Islands waters were sampled for their foraminiferal fauna at six sites i.e. Nasik Strait (four sites), Kudus Island and Bago Island on April 2010. Results of benthic foraminiferal quantitative analysis of the sediments in which collected from six sampling sites of Belitung Islands show that totally collected specimens 29 species of 18 genera. The most favorable place for coral growth is the free area (absence of coral, mangrove and seagrass) of Nasik Strait, but it only has 30 specimens of benthic foraminifera, with three species of symbiont-bearing foraminifera such as Operculina and Amphistegina. Whereas, the most abundant of benthic foraminifera is Nasik Strait 1 with typical substrate coarse sand and vegetated by coral reef. In other side, segrass bad of Nasik Strait is dominated by opportunistic foraminifera and only dwelled by Heterostegian, Calcarina, Elphidium, Ammonia, Acervulina, Spirolina, Quinqueloculina and Lenticulina. Moreover, the most abundant species of all sampling sites is Peneroplis pertusus.